Spatiotemporal evolution and development path of healthcare services supply in China - Xiang-Min Li (BMC, 2024)
Abstract Object Promoting the accessibility and equity of healthcare services, as well as enhancing service capacity, are crucial for building a sound healthcare system. Particularly in the past two years of the normalized COVID-19 situation, this issue has garnered widespread attention in the academic community. This study aims to investigate and analyze the characteristics and trends of the spatial-temporal evolution of healthcare service supply levels in China. It also seeks to explore the influencing factors and pathways for development, with the goal of optimizing the allocation of healthcare resources. Methods This article uses the entropy weight TOPSIS method combined with Dagum Gini coefficient and Kernel density to evaluate the supply level of healthcare services in 31 provinces and cities in China from 2012 to 2020, and explores its development and spatial pattern characteristics. Then, through Moran index, panel regression model and spatial econometric testing, the spatial correlation problem and its influencing factors are further analyzed, and targeted policy recommendations are proposed based on it, laying the foundation for further promoting the balanced development of healthcare service supply capacity. Results (1) Healthcare services supply levels in various provinces and cities in China have significantly increased, with a shift in spatial distribution from 'higher in the east and lower in the west' to 'convergence between east and west, with lower levels in the central regions.' (2) Relative differences among regions are narrowing annually, primarily due to interactions between the four regions rather than within each region, with expanding impact of overlapping regions. (3) Absolute differences among regions are also decreasing, moving towards uniformity with a contraction of extension and a restraint on the trend towards multipolarization. (4) Spatial correlation between adjacent regions is weakening, eventually becoming non-significant, with fading spatial effects. (5) The correlation between local economic development, population factors, institutional arrangements, and the current state of supply is significant, and the research design and conclusions remain robust even after thorough consideration of spatial effects. The study explores the development pathways based on the objective existence of regional development and the controllable government actions. Conclusion The overall level of healthcare service supply in China has improved, but regional differences still exist. The objective level of regional development and the subjective behavior of local governments have a significant impact on the supply of healthcare services. Therefore, it is recommended that each region adapt to local conditions, identify its own strengths and weaknesses, coordinate resource supply and demand, consider the impact of key factors, and optimize the allocation of healthcare development resources.